2023
DOI: 10.3390/su15086917
|View full text |Cite
|
Sign up to set email alerts
|

Promising Emerging Technologies for Teaching and Learning: Recent Developments and Future Challenges

Abstract: As time goes on and the number of people who use information and communication technology (ICT) grows, emerging technologies are receiving a lot of attention from academics, researchers, and users. Emerging technologies are changing more quickly than ever, and it is important to start building skills early in education by using the right examples to teach and learn about digital citizenship. New pedagogies support individual teaching and learning methodologies for knowledge acquisition and self-directed learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…The current study utilized SmartPLS 4.0 to derive Cronbach’s alpha and composite reliability values to indicate internal consistency between items and constructs. The study showed that the values of Cronbach’s alpha coefficient and composite reliability were greater than 0.7, indicating that the data collection instrument was internally consistent with the items ( Hair et al, 2020 ; Almufarreh and Arshad, 2023 ), and as shown in Table 5 , the values of Cronbach’s alpha coefficient and composite reliability both passed, proving that the items for each variable were internally consistent and reliable. Second, this study measured construct validity by extracting the average variance, and the literature suggests that the AVE values are at least 0.5 or higher, assuming that each variable meets the criterion for construct validity ( Hair et al, 2020 ; Almufarreh and Arshad, 2023 ), as shown in Table 5 , the AVE values are all greater than 0.5, indicating good construct validity.…”
Section: Research Design and Methodologymentioning
confidence: 87%
“…The current study utilized SmartPLS 4.0 to derive Cronbach’s alpha and composite reliability values to indicate internal consistency between items and constructs. The study showed that the values of Cronbach’s alpha coefficient and composite reliability were greater than 0.7, indicating that the data collection instrument was internally consistent with the items ( Hair et al, 2020 ; Almufarreh and Arshad, 2023 ), and as shown in Table 5 , the values of Cronbach’s alpha coefficient and composite reliability both passed, proving that the items for each variable were internally consistent and reliable. Second, this study measured construct validity by extracting the average variance, and the literature suggests that the AVE values are at least 0.5 or higher, assuming that each variable meets the criterion for construct validity ( Hair et al, 2020 ; Almufarreh and Arshad, 2023 ), as shown in Table 5 , the AVE values are all greater than 0.5, indicating good construct validity.…”
Section: Research Design and Methodologymentioning
confidence: 87%
“…The importance of English courses is increasing, and relevant professionals have investigated in-depth college students learn English on their terms and suggested appropriate personalized English learning strategies employing IoT and big data analysis. In this paper [13], the authors provided an in-depth architecture for an IoT-enabled platform for studying college English that enables personalized learning experiences using data analytics. Depending on student data analysis, machine learning algorithms can quickly customize instructional materials and feedback.…”
Section: Related Workmentioning
confidence: 99%
“…All forms of learning process can be carried out easily because of technological assistance. According to (Almufarreh & Arshad, 2023) technological advancements have significantly influenced the education landscape, propelling traditional teaching methodologies into immersive and interactive learning experiences. Researchers continued comparing newly developed technologies to traditional media hoping for an educational revo-lution because now this technology will change learning fundamentally (Bozkurt, 2020).…”
Section: Introductionmentioning
confidence: 99%